A Prospective and Observational Study to Assess the Hematological Toxicities of Concurrent Chemoradiation Therapy Inpatients with Locally Advanced Cancersin a Tertiary Care Teaching Hospital - Ramayanam, Navakanth Raju (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: Cancer ranks as the second most prevalent non-communicable disease worldwide, urging exploration into acute and late chemoradiation-induced hematological toxicities in patients with head-and-neck cancer (HNC) and uterine cervix cancer (UCC). Material and Methods: Our prospective observational study, conducted in a tertiary care teaching hospital, enrolled 60 cancer patients aged over 18 years. Utilizing the National Cancer Institute Common Terminology Criteria for Adverse Events, we assessed toxicity levels. Results and Discussion: Results revealed a gender disparity, with females exhibiting higher frequency (73.3%), and the highest frequency occurring among individuals aged 41–50 years (36.7%). Comparing tumor types, HNC exhibited lower carcinoma incidence than UCC (68.3%). Hematological profiles during chemoradiation therapy revealed Grade 1 anemia (24%) in the 1st week and Grade 3 toxicities in subsequent weeks. Notably, Grade 5 toxicity and Grade 1 thrombocytopenia (23%) were observed. Grade 1 neutropenia was predominant in the 2nd–4th weeks (21%), while additional cases of Grade 1 lymphocytopenia surfaced in the 2nd week. Grade 4 toxicities peaked in the 1st and 3rd weeks (29%), with leucopenia prevalent in the 3rd week (13.3%). Conclusion: While these toxicities are generally manageable and self-limiting, vigilance is warranted to avert severe complications like febrile neutropenia and anemia, emphasizing the need for prompt intervention to prevent life-threatening outcomes.